An Empirical Rate Constant Based Model to Study Capacity Fading in Lithium Ion Batteries - Srivatsan Ramesh; K. Venkata Ratnam; Balaji Krishnamurthy (International Journal of Electrochemistry)
A one-dimensional model based on solvent diffusion and kinetics to study the formation of the SEI (solid electrolyte interphase) layer and its impact on the capacity of a lithium ion battery is developed. The model uses the earlier work on silicon oxidation but studies the kinetic limitations of the SEI growth process. The rate constant of the SEI formation reaction at the anode is seen to play a major role in film formation. The kinetics of the reactions for capacity fading for various battery systems are studied and the rate constants are evaluated. The model is used to fit the capacity fade in different battery systems.